Marine Tourism's Economic Impact on Sustainable Livelihoods in Mombasa County, Kenya - Ochieng, Shirley Natasha; Bitok, Kipkosgei; Muthingi, Sisinio (Goodwood Publishing, 2025)
Abstract Purpose: This study aimed to explore how economic aspects of marine tourism influence the sustainable livelihoods of communities in Mombasa County, Kenya. Methodology/approach: The study was conducted in Mombasa County, Kenya, using a mixed-methods approach guided by sustainable tourism development theory and stakeholder theory. Quantitative data were collected using structured questionnaires from 384 community members and analyzed using SPSS version 23 for regression and descriptive statistics. Qualitative data were gathered through in-depth interviews with 73 key informants, including beach operators and tourism officials, and analyzed thematically. Results/findings: The findings indicated a statistically significant positive relationship between the economic aspects of marine tourism and sustainable livelihoods. Limitations: The study's cross-sectional design limits its ability to capture long-term changes, and its focus on Mombasa County may limit the generalizability of the findings to other coastal communities. Contribution: This study contributes to the fields of tourism management, sustainable development, and coastal management by providing empirical evidence on the economic impacts of marine tourism. It offers valuable insights for policymakers, tourism stakeholders, and local communities in Mombasa County and similar coastal regions. Novelty: The novelty of this study lies in its integrated approach, combining quantitative and qualitative methods to provide a holistic understanding of how marine tourism influences sustainable livelihoods. Additionally, it emphasizes the importance of tourism policies in shaping the outcomes of marine tourism development. Keywords: Marine tourism, sustainable livelihood, economic aspects, Kenya